PENGARUH LATIHAN DOUBLE LEG RUN LADDER TERHADAP KELINCAHAN TENDANGAN SAMPING PADA ANGGOTA TARUNG DERAJAT - Jamaludin Jamaludin (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2017)
To improve the performance of the sport of fighting degree of course is supported by the physical ability, technique, tactics and strategic in fighting. Physical ability is the basic capital that each athlete must have, so in every coaching program it always starts with an emphasis on physical training of every athlete. Adpun one of the indicators of physical condition that is needed is good agility kicks and punches, so it takes a special training especially those associated with kicks. In connection with it can be formulated a problem that is there any influence of Double Leg Run Ladder Exercise Against Agility Side Cycling In Tarung Derajat Mamben Lombok Timur Year 2017? Based on that, the purpose of this research is to know the effect of Double Run Leg Run Ladder Exercise Against Agility on Side Sampling at Tarung Derajat Mamben Lombok Timur Year 2017. To reach the goal, the researcher uses quantitative method and action test with one group design pree test poos test , and the number of samples used in this study were as many as 20 people and the data analysis used was an inferential statistical technique with the t-test formula. Based on the results of data analysis in this study it can be drawn a conclusion that "There is Influence of Double Leg Run Ladder Exercise Against Agility Side Attack On Member Tarung Degrees Mamben East Lombok Year 2017